Novel Electrochemical Sensor Based on MnO2 Nanowire Modified Carbon Paper Electrode for Sensitive Determination of Tetrabromobisphenol A - Chunmao Zhu; Qi Wu; Fanshu Yuan; Jie Liu; Dongtian Wang; Qianli Zhang (Chemosensors, 2023)
In this paper, a MnO2 nanowire (MnO2-NW) modified carbon paper electrode (CP) was developed as a novel electrochemical sensor for the sensitive determination of tetrabromobisphenol A (TBBPA). The MnO2 nanowire was prepared by a hydrothermal synthesis method, and the morphology and structure of MnO2 were characterized using scanning electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. The electrochemical performance of TBBPA on MnO2-NW/CP was investigated by cyclic voltammetry, and the result confirmed that MnO2-NW/CP exhibited excellent sensitivity for the determination of TBBPA due to the high specific surface area and good electrical conductivity of the nanowire-like MnO2. Moreover, the important electrochemical factors such as pH value, incubation time and modified material proportion were systematically studied to improve the determination sensitivity. The interferences from similar structure compounds on TBBPA have also been investigated. Under the optimal conditions, MnO2-NW/CP displayed a linear range of 70~500 nM for TBBPA with a detection limit of 3.1 nM. This was superior to some electrochemical methods in reference. The work presents a novel and simple method for the determination of TBBPA.